Analisis Butir Soal Pilihan Ganda Menggunakan Anates pada Penilaian Tengah Semester Kelas VII D SMP Negeri 1 Ngajum Kabupaten Malang - muh sholeh mawardi; Anies Fuady; Sunismi Sunismi (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
Evaluation or assessment of learning is one part of a series of learning processes. A quality assessment device is able to measure what will be measured. In fact not all teachers do an analytical test first before the manuscript test is used. Analysis of question items is a series of activities carried out in assessing the quality of question items. Validity provides an idea which the assessment tool can measure exactly what is to be measured. The reliability of an assessment tool is to measure the extent to which the measurement results with the assessment tool are stable or consistent. Anates is an application or software developed to help carry out the analysis of question items quickly and practically. A study was carried out with the title